Agenda driven mobility modelling. (4th December 2009) - Zheng, Qunwei; Hong, Xiaoyan; Liu, Jun; Cordes, David; , Wan Huang
Mobility modelling is an essential component of wireless and mobile networking research. Our proposed Agenda Driven Mobility Model takes into consideration a person's social activities in the form of agenda (when, where and what) for motion generation. The model provides a framework for translating social agendas into a mobile world. Using the data from National Household Travel Survey (NHTS) of the US Department of Transportation, our simulation results suggest that social roles and agenda activities tend to cause geographic concentrations and significantly impact network performance. The model is in a position of better reflecting real world scenarios.